Role of Bioenzyme as Catalyst for Sustainable Chemistry - Ghuge Samiksha K; Khaire Rahul; Kathale Ankita A; Sankhe Lochani D; Bhandare Tejaswini S; Koade Payal B (Asian Journal of Pharmaceutical Research and Development, 2025)
The integration of bio enzymes as catalysts represents a pivotal strategy for advancing sustainable chemistry. Enzymes, as natural biocatalysts, offer high specificity, operate under mild conditions, and generate minimal by-products, aligning closely with the principles of green chemistry. Their biodegradability, renewability, and compatibility with aqueous systems enable environmentally friendly processes across pharmaceutical, food, textile, and chemical industries. Innovations in enzyme engineering, bioinformatics, and artificial intelligence have enhanced catalytic efficiency and stability, expanding enzyme applications to include nanozymes and tailored industrial bioprocesses. Immobilization techniques—such as adsorption, encapsulation, covalent bonding, and cross-linking—further improve enzyme reusability and cost-effectiveness, addressing industrial demands. Emerging fields like metagenomics facilitate the discovery of novel enzymes from uncultured microorganisms, unlocking new biocatalytic pathways. Bio enzyme-based treatments also provide eco-efficient solutions for wastewater remediation by degrading organic pollutants and reducing heavy-metal content. Together, these developments underscore the transformative role of bio enzymes in replacing traditional chemical reagents, minimizing waste, and reducing energy inputs. By coupling biotechnology with sustainable chemical practices, bio enzymes stand as a cornerstone for a greener, circular economy and the realization of global sustainability goals.